Long - chain branched polypropylenes obtained by copolymerization with use of metallocene catalysts - Kaminsky, W.; Rulhoff, S. (Polimery, 2022)
Metallocene/methylalumoxane catalysts can be used to synthesize macromonomers of ethylene as well as copolymers of propene with macromonomers. In the experiments Me2C(Cp)2ZrCl2 is used which let polymerize ethylene to macromonomers but is unable to cause propene polymerization. After addition of Ph2C(Cp)(Flu)ZrCl2 and propene, long chain branched polypropylenes are produced with isotactic, syndiotactic or atactic backbone. The differences of crystalline or amorphic polypropylene backbone with crystalline polyethylene side chains were investigated. It was shown that the melting temperature (Tm) decreases strongly with increasing concentration of macromonomers in the copolymers. To reduce the melting point by 20°C 0.1 mol. % of macromonomers is sufficient.